IMPROVING SPREADSHEET SKILLS: THE ROLE OF DIGITAL LITERACY, LEARNING STYLE, AND EMOTIONAL INTELLIGENCE IN CLASS X ACCOUNTING STUDENTS - Fatimah; Respati, Dwi Kismayanti; Zulaihati, Sri (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The purpose of this study was to determine the effect of digital literacy, learning styles and emotional intelligence on student learning outcomes in the Spreadsheet subject. The research conducted was quantitative research. The population of this study was class X Accounting students at three Public Vocational High Schools in the Jakarta area, which was 214 students. The selected sample was 115 students as respondents, then students were selected using random sampling techniques. The data were analyzed using the SPSS 27 program. Data analysis techniques were carried out through normality tests, multiple linear regression tests, hypothesis tests and coefficients of determination. The results of the study showed that: There is a significant influence between digital literacy on learning outcomes, there is a significant influence between learning styles on learning outcomes, there is a significant influence between emotional intelligence on learning outcomes, there is a significant influence between digital literacy, learning styles and emotional intelligence on learning outcomes.